The Relationship between Body Image with Eating Disorder in Medical Student - Devina Nahama Natarijadi; Titis Hadiati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Adolescence is a critical stage when a person experiences a fast and significant changes in their physic, cognitive, emotion and social. This changes affect their body image. Body image dissatisfaction leads them to do anything, even by changing their eating behaviour, to have a body goal. This behaviour can leads to an eating disorder.Objective: To know the relationship between body image perception with the incidence of eating disorders in medical students.Methods: An observational study with a cross sectional design on 240 students of the Medical Faculty of Diponegoro University 2019 using the Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) test for scoring the body image and Eating Attitude Test-26 (EAT-26) for scoring the eating disorder.Results : Body image perception, Negative evaluation appearance 148 persons (61,67%). Negative appearance orientation 199 persons (82.91%). Negative body area satisfaction 167 persons (69,58%). Negative overweight preoccupation 137 persons (57,08%). Negative self-classified weight 102 persons (42,50%). Eating disorders, 19 persons (7,9%) had risk of eating disorders. Positive appearance orientation had a significant effect on the incidence of eating disorders. p < 0,05, OR = 3, dan CI95% = 0.115 – 0.848. Positive overweight preoccupation had a significant effect on the incident of eating disorders. p < 0,05, OR = 4 , dan CI95% = 0.084 - 0.692.Conclusion: There is relation between body image on appearance orientation subscale and overweight preoccupation subscale with eating disorders.Keywords : adolescence, body image, eating disorder